Пародийный пересказ Дон-Аминадо об эмиграции и эмигрантах - Joanna Mianowska (Studia Rossica Posnaniensia)
Among the group of Russian emigrants in the 20th century, after the October Revolution, were many famous satirists and humorists, for example, A. Averchenko, Sasha Cherny, N. Teffi, V. Goryansky, Don-Aminado and many other acclaimed masters of satire. Attention is focused on a mock novelette about emigration and emigrants that was written by the so-called “new Kozma Prutkov” – a forgotten satire writer Don-Aminado (real name: Aminad Petrovich Shpolyansky). The year 2012 marked the 55th anniversary of his death. This article examines Don-Aminado’s aphorisms and a mock novelette about his fellow countrymen in France. The experience the satirist gained from his wanderings after he had emigrated from Russia let him re-evaluate many things and allowed him to make fun of himself, his friends and the fact that, by a stroke of fortune, they came to Paris. The existence of a “little man”, i.e. a Russian emigrant in France, his/her poverty, debts, the privation he/she suffered, the lack of professional job offers and the fact that he/she lived on credit was the major theme in Don-Aminado’s satire. Don-Aminado is said to be Kozma Prutkov’s successor as regards his poetic parodies, maxims and aphorisms that are applicable to life, which is the secret of their longevity.